Phytochemical constituents from Calophyllum buxifolium Vesque and Calophyllum hosei Ridl and their biological activities - Daud, Shaari (2017)
Extensive phytochemical and biological studies to search for bioactive secondary metabolites from our Malaysian flora stem bark of two Calophyllum spp., C. buxifoliumand C. hosei were carried out. These two plants were subjected to detail isolation work which involved extraction and purification of chemical components using various chromatographic techniques. All the pure compounds were identified using numerous spectroscopic analysis, such as 1D and 2D NMR, MS, IR, UV and also by comparison with literature data. These techniques have led to the isolation and elucidation of several chemical constituents of different type of classes which are the xanthones, coumarins, flavonoid, terpenoid and sterols. The crude extracts and several pure compounds from both plants species were also screened for their cytotoxic, anti-inflammatory and antimicrobial activities using MTT (Microculture Tetrazolium Salt), nitric oxide (NO) and disc diffusion assay. Human promyelocytic leukemia (HL60) and human breast adenocarcinoma (MCF7) cell lines were used in the cytotoxic assay. The anti-inflammatory activity was tested against RAW 264.7 murine macrophage cells in vitro that were treated with lipopolysaccharide (LPS) which induce inflammatory response. The antimicrobial activity was tested against three Gram positive bacteria, Bacillus subtilis B145, Staphylococcus aureus S276 and Staphylococcus epidermis S273 and two Gram negative bacteria, Escherichia coli E266 and Serratia marcencensS381. Detail work on the stem bark of C. buxifolium a plant never reported before for its phytochemistry has led to the isolation of two new chemical components, buxixanthone (215) and benjaminin (223) together with another 14 known compounds that consists of xanthones, flavonoids and terpenoids. Meanwhile from the study on three different extracts from the stem bark of C. hosei also an unreported plant, has successfully result in one new coumarin, hoseimarin (222) along with other 12 known xanthones and one common triterpenoid. There has been no previous report on the phytochemical work on the C. hosei. The crude extracts for both plants gave a weak cytotoxic activity through MTT assay against two human cancer cell lines, HL60 (human promyelocytic leukemia) and MCF7 (human breast adenocarcinoma) cell line. Only four compounds, benjaminin (223), mangostingone (220), rubraxanthone (221) and β-mangostin (178) gave some activities towards the HL60 cell line with IC50 values of 96.13, 46.92,10.53 and 7.16μg / mL, respectively. Anti-inflammatory assay was carried out for the crude extracts and 14 pure compounds using the nitric oxide (NO) assay. Most of the crude extracts for both plants gave a weak inhibition of NO production in RAW 264.7 cells. Eight xanthones, rubraxanthone (221), buxixanthone (215), ananixanthone (183), dombakinaxanthone (95), macluraxanthone (87),β-mangostin (178), 1,3,7-trihydroxy-2-(3-methylbut-2-enyl)-xanthone (218) and mangostingone (220)gave IC50 values of 6.45, 6.84, 7.14, 7.57, 9.07, 11.68, 12.05 and 12.34 μg / ml indicating their strong efficacy in reducing the NO production in RAW 264.7 cells. On the other hand, six more pure compounds gave mild inhibition on NO production in RAW 264.7 cells. All the crude extracts for C. buxifolium and C. hosei gave no inhibition towards three Gram positive bacteria, Bacillus subtilis B145, Staphylococcus aureus S276 and Staphylococcus epidermis S273 and two Gram negative bacteria, Escherichia coli E266 and Serratia marcencens S381.